The Reality of Competitive Advantage in the Ministry of Education in the Sultanate of Oman in the Context of Oman Vision 2040 - Alhabsi, Radhiya Sulaiman Nasser; Alfawair, Ahmad MJ O (International Journal of Membrane Science and Technology, 2023)
This study aimed to assess the level of competitive advantage in the Ministry of Education in the Sultanate of Oman, in the context of Oman Vision 2040. A total of 257 employees from the Ministry of Education in Oman participated in the study. The analytical descriptive approach was used, and a questionnaire comprising 31 items was distributed among the participants to assess the quality of educational services, distinguished human resources, material and financial resources, and the pursuit of institutional excellence. The study found that the level of competitive advantage in the Ministry of Education in Oman was "average", with the quality of educational services dimension having the highest level and the distinguished human resources dimension having the lowest level. The study also revealed statistically significant differences in the responses due to qualification and years of experience. However, there were no statistically significant differences due to gender and nature of work. Based on the results, the study recommends the enhancement of competitive advantage in the Ministry of Education in Oman by improving the quality of educational services, developing human resources, improving management and strategic planning, and focusing on developing and modernizing educational programs to meet the needs of the labor market and the requirements of the times in light of Oman Vision 2040.